Epidemiological analysis of Acute Respiratory Infections in children and adults treated in the emergency rooms of the main hospitals of Maputo city - Mozambique, 2019-2020 - Fabião Maússe; Samuel Nuvunga; Auria Banze; Judite Braga; Liliana Balói; Cynthia Baltazar; Erika Rossetto (Journal of Interventional Epidemiology and Public Health)
Introduction: Acute respiratory infections (ARI) prevent the normal functioning of the upper and lower respiratory tract. Mozambique established sentinel surveillance for ARIs in 2013 to produce consistent data and information for decision-making. The study descriptively analyzed the data from the ARI surveillance system in Maputo city from May 2019 to February 2020.